Taking Away the Pound : Women, Theology and the Parable of the Pounds in the Gospel of Luke. - Dowling, Elizabeth V. (Library of New Testament studies., 2007)
Against the majority opinion, this study argues that the Lukan Parable of the Talents (Lk 19.11-28) is a story about the use and abuse of power. The parable is also the story of those who suffer adverse consequences when they oppose unjust power structures. This suppression of challenge to oppressive structures evidenced in the Parable of the Pounds fits a pattern that operates in other parts of the Lukan Gospel. We meet it, for example, in the arrest and killing of John the Baptist by Herod, and in the arrest and crucifixion of Jesus. The Parable of the Pounds can be seen as a paradigm for th.